Young scientists science camp STEM-based as an effort to increase the competency of students in the Zainul Hasan Genggong Islamic boarding school - Ahmad Taufiq; Arif Hidayat; Hadi Suwono; Ainun Nikmah; ST. Ulfawanti Intan Subadra; Lya Rizka Herawati (Community Empowerment, 2024)
The aim of this service is to increase the competency of students in the Zainul Hasan Genggong Islamic Boarding School, especially in the field of science. The method used in implementing this activity includes three stages, namely field survey and preparation, Young Scientists Science Camp activities, and the monitoring stage. Selected students are given training in selecting relevant research topics, involved in research in university laboratories, and guided in the preparation of scientific papers. Through this stage, participants are given hands-on training in scientific research and the use of technology. The output of this activity is in the form of 1 scientific article which was presented at the international scientific forum International Conference on Advanced Technology and Multidiscipline (ICATAM). Through this activity, it is hoped that participants' skills in research, use of technology and software will increase. Apart from that, participants can have insight into preparing scientific papers. This program is expected to contribute to improving participants' critical and creative thinking abilities, which are important aspects in facing changes in the industrial revolution 4.0. So this Young Scientists Science Camp program will make a valuable contribution in preparing the young generation with relevant skills for a future that is increasingly influenced by technology and global change.